Klimkówka Lake in Beskid Niski – geotouristic aspects - Waśkowska, Anna; Golonka, Jan; Witkowska, Elżbieta (Geotourism/Geoturystyka, 2014)
The Klimkówka Lake geotouristic site is one of the greatest attractions of the Beskid Niski Mountains of the Polish Carpathians Mts. Nearly 20 years of existence of the artificial dam lake generated the development of tourism in the area. The great advantage of Klimkówka Lake region is the presence of a number of spectacular surface rock outcrops situated in convenient locations for visitors, in which crop out the youngest rocks of the Rača Zone of the Magura Nappe. The area around the Klimkówka Lake is a great training ground to acquire knowledge of the geology of the Outer Carpathians, as well as different varieties of sedimentary rocks, and sedimentary and tectonic structures.